2019
DOI: 10.3390/ma12244105
|View full text |Cite
|
Sign up to set email alerts
|

Parametric Analysis of the Mandrel Geometrical Data in a Cold Expansion Process of Small Holes Drilled in Thick Plates

Abstract: Cold expansion technology is a cold-forming process widely used in aeronautics to extend the fatigue life of riveted and bolted holes. During this process, an oversized mandrel is pushed through the hole in order to yield it and generate compressive residual stresses contributing to the fatigue life extension of the hole. In this paper, a parametric analysis of the mandrel geometrical data (inlet angle straight zone length and diametric interference) and their influence on the residual stresses was carried out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 13 publications
1
7
0
Order By: Relevance
“…For the specific case of the mandrel geometry, there are a wide published research focused on the tapered models [13][14][15][16] but limited investigations on ball geometries [17,18]. The motivation behind the use of ball geometries, as an alternative to tapered mandrels, comes from its consolidated manufacturing process based on their use for ball bearings industry.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…For the specific case of the mandrel geometry, there are a wide published research focused on the tapered models [13][14][15][16] but limited investigations on ball geometries [17,18]. The motivation behind the use of ball geometries, as an alternative to tapered mandrels, comes from its consolidated manufacturing process based on their use for ball bearings industry.…”
Section: Introductionmentioning
confidence: 99%
“…Calaf-Chica et al [13] showed the significance of selecting the optimal geometry for tapered mandrels. Three parameters were targeted: length of straight zone (SZ), inlet angle (IA) and outlet angle (OA) (see Figure 7).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In this Special Issue of the journal Materials, 29 contributions to cutting-edge advances in different fields of the manufacturing engineering have been collected. In particular, in additive manufacturing and 3D printing [4][5][6][7][8][9][10][11]; sustainable and green manufacturing [12][13][14][15][16]; metrology and quality in manufacturing [17][18][19][20][21]; advances and innovations in manufacturing processes [22][23][24][25]; manufacturing of new materials [26][27][28]; design, modeling, and simulation in manufacturing engineering [29,30] industry 4.0 [31] and manufacturing engineering and society [32]. Among all of them, the topic additive manufacturing and 3D printing stands out for the number of contributions it has had in this Special Issue showing the interest that this topic arouses, currently, among researchers, the industry and the public in general.…”
mentioning
confidence: 99%
“…Concretely, two about thermoplastic carbon fiber composites C/TPU [26,27] and, other, about an Al-SiC metal matrix composite [28]. It counts also with two works in design, modeling, and simulation in manufacturing engineering about the indentation process [29] and the cold expansion process [30]; one, in the topic industry 4.0 about the application of the supply chain to shipbuilding [31] and the other in the topic manufacturing engineering and society about a new risk methodology based on control charts to assess occupational risks in manufacturing processes [32].…”
mentioning
confidence: 99%